2023
DOI: 10.5114/biolsport.2023.116451
|View full text |Cite
|
Sign up to set email alerts
|

On-court throwing activity of male handball players during the European Championship 2020

Abstract: The aim of this study was to investigate the on-court throwing activity in regards to playing positions, throwing zones on the court and throwing velocity category during the male European Championship 2020. A local positioning system with microsensors placed both in the shirts of the players and inside the ball itself was used. In total, 6568 throws were retrieved for analysis from the entire tournament. Results showed that first-line players (wings and line players) used their natural zone more to throw (65%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In the official statistics of the PGNiGSuperleague Ltd. regarding shots taken and goals scored, it is not recorded from which positions they were taken and from which zones of the court. Previous research results indicate differences in the number and effectiveness of throw-ins in relation to the position and location from which the throw-in is made (Pueo et al, 2022(Pueo et al, , 2023. Therefore, it should be concluded that the lack of these data is one of the limitations of the results presented in this publication.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the official statistics of the PGNiGSuperleague Ltd. regarding shots taken and goals scored, it is not recorded from which positions they were taken and from which zones of the court. Previous research results indicate differences in the number and effectiveness of throw-ins in relation to the position and location from which the throw-in is made (Pueo et al, 2022(Pueo et al, , 2023. Therefore, it should be concluded that the lack of these data is one of the limitations of the results presented in this publication.…”
Section: Discussionmentioning
confidence: 76%
“…They lack reference regarding the location and tactical situation of throws in the context of the position and sector of the field. Previous research indicates that these are factors that differentiate the number and effectiveness of throws (Pueo et al, 2022(Pueo et al, , 2023. A specific limitation of the present study is also the lack of information on the implemented training content, especially during the COVID-19 pandemic.…”
Section: Limitationsmentioning
confidence: 84%
“…Similarly, there is a higher tendency for second-line players to finish the play, with the final goal percentage being above 58% ( Table 4 ). However, a higher team ranking was associated with higher throwing efficiency, but only for wingers ( Pueo et al, 2023 ).…”
Section: Discussionmentioning
confidence: 96%
“…The obtained results correspond with recent reports [27], which indicate a trend in the offensive play of teams focusing on finalizing the action with throws from 6 meters. It should also be pointed out that throws made from closer distances show higher efficiency [24,25,27]. Such a condition may indicate the implementation of offensive actions, which create the possibility of obtaining the highest sports score within a single match.…”
Section: Discussionmentioning
confidence: 99%